Activities and practices in creative tourism: examples of international institutions - Remoaldo, Paula (2019)
In recent years, the cultural tourist has demanded more direct contact with the culture of the community he is visiting. On the other hand, tourism destinations, especially small cities and rural areas, need to attract more visitors, enhance, value and promote tourist resources and create more innovative, differentiating and authentic tourist products (Richards & Raymond, 2000; Richards, 2011). In 2000, a new tourism segment emerged that could offer visitors the opportunity to co-create and develop their creative potential and that promotes deep contact with the culture of community of destination. We are talking about creative tourism. However, up to the present, it has been difficult to reach consensus on the definition. As it is important to know how networks and platforms are being developed dealing with this kind of tourism, an investigation was carried out between July 2017 and October 2018 to identify and analyse existing practices at international scale. This investigation was done within the scope of the CREATOUR project: Creative Tourism Destination Development in Small Cities and Rural Areas, funded under the joint activities of the Portugal 2020 and the FCT. In first place was done a research on Google (web) from March to August 2017. From this research, we concluded that there are 24 institutions by using the Keywords. “creative tourism initiatives”, “creative cities”, and “best practices in creative tourism”. In a second phase we created a database of 20 items using indicators for each institution such as year of implementation, site, developed activities, place of development, and type of partners chosen and local community involvement. In another research perspective, each of its sites was analysed, from September to December 2017, to try to understand each one of their websites were analysed from September to December 2017 to understand the kind of products provided, the languages used during the workshops that were organized, and the public and the type of professionals that taught those same workshops. On the last phase (from July 2017 to October 2018) some semistructured interviews were applied to managers or representatives of the institutions. They were conducted mainly via Skype and a guide of 17 questions was used structured in 10 thematic groups. The main results of the interviews show that institutions will continue to increase the quality of creative initiatives, promote and disseminate culture in all creative initiatives, improve communication channels and stimulate partnerships to organize innovative initiatives.